(untitled) (Journal of Science Foundation, 2013)
The study was carried out from November 2010 to August 2011. A total of 137 specimens of Cyprinus carpio var. specularis were collected from Naogaon municipal fish market, Shabi hat fish market, Niamatpur fish market and directly from the culture pond of Naogaon district The month-wise collection and experiments were made to show the seasonal variation in food choice, and feeding habit of the fish. The highest percentage of empty stomach was in the month of April 2011 (56.67%) and the lowest percentage of empty stomach was in the month of August 2011 (26.32%). The highest percentage of full stomachs was found in the month of August 2011 (73.68%) and the lowest percentage of full stomachs was found in April 2011 (43.33%). The analysis of stomach contents of C. carpio var. specularis revealed that the food of the fish consists of aquatic plant parts (20.12%), phytoplankton (16.46%), zooplankton (19.69%), debris and detritus (22.00%), insects (6.78%) and semi-digested materials (14.83%). The highest percentage (33.26%) of aquatic plant parts were observed in June 2011 and the lowest percentage (8.80%) in December 2010. The average total length was 37.83±6.96 cm and the average alimentary canal length was 100.63±7.89 cm. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14658 J. Sci. Foundation, 9(1&2): 163-169, June-December 2011